Patients with Single Ventricle Anatomy May Respond Better to Octreotide Therapy for Chylothorax After Congenital Heart Surgery. Issue 2 (4th December 2013) - White, Shelby C.; Seckeler, Michael D.; McCulloch, Michael A.; Buck, Marcia L.; Hoke, Tracey R.; Haizlip, Julie A.
Abstract Background and Aims Chylothorax (CTX) occurs in 3% to 6% of children after surgery for congenital heart disease with significant morbidity and mortality. Octreotide has been proposed as therapy, but there are no predictors of response. The objective of this study was to identify possible predictors of response to octreotide. Methods Single‐center retrospective review of patients who developed CTX after cardiac surgery. Data collected included demographics, cardiac lesion, surgical data, hospital course, CTX volume and duration, and interventions for CTX. Patients who received octreotide as part of their therapy were compared to those who did not. Results A total of 1150 patients underwent 1455 cardiac surgeries with 67 (4.6%) episodes of CTX. Patients with CTX were younger, lower weight, more likely to undergo cardiopulmonary bypass, and had higher RACHS‐1 scores and mortality. Nineteen patients with CTX received octreotide as part of their treatment and six (32%) had at least 50% reduction in CTX volume. Patients who responded to octreotide had lower CTX volume (18 mL/kg/day vs. 55 mL/kg/day, p = 0.023) and a higher proportion of patients with single ventricle anatomy (67% vs. 18%, p = 0.046). Conclusions There is a subset of patients who seem to respond to octreotide, but they have lower CTX volume and may have already been improving before octreotide therapy. Patients with single ventricle anatomy seemed to respond to octreotide and may benefit from its use. doi: 10.1111/jocs.12263 (J Card Surg 2014;29:259–264)